Determinants of Intention to Choose Islamic Banks: Trust, Reputation, Literacy, and Religiosity - Febriyani, Nurlatifa; Alrasyid, Harun; Rizal, Mohammad (JPS (Jurnal Perbankan Syariah), 2026)
Purpose: This research investigates how trust, institutional reputation, and Islamic financial literacy shape behavioral intentions to select Islamic banking services among the Sumenep community, while also examining the moderating role of religiosity. Method: The study adopts a quantitative explanatory design and applies Partial Least Squares–Structural Equation Modeling (PLS-SEM) for empirical analysis. Data were collected from 276 respondents selected through purposive sampling. Findings: The results demonstrate that trust, reputation, and Islamic financial literacy significantly affect individuals’ intentions to choose Islamic banks. In addition, religiosity functions as a moderating factor that diminishes the influence of reputation on behavioral intention. Implications: From a theoretical perspective, this study contributes to the extension of the Theory of Planned Behavior in the context of Islamic financial decision-making by positioning religiosity as a contextual influence rather than a direct moderator within the core TPB constructs. From a practical standpoint, the findings highlight the importance of building public trust, strengthening the credibility of Islamic banking institutions, and enhancing Islamic financial literacy to encourage greater adoption of Islamic banking services.